The Effectiveness of Offline and Online Pregnant Women Classes on Knowledge of High-Risk Pregnant Women - Sherly Marliena; Andi Lis Arming Gandini; Nino Adif C (PT FORMOSA CENDEKIA GLOBAL, 2023)
Efforts to reduce maternal mortality need to be carried out by early detection of high-risk pregnancies at maternal and child health services or in the community. Method: Quasi experimental research method non-equivalent control group design. Results: Based on an analysis of differences in mothers' knowledge about high-risk pregnancies in the Intervention group and the Control Group in the Gunung Bahagia Health Center area in 2022, the results obtained were p-value (0.074) > 0.05, which means there was no difference in the knowledge of respondents in the Pregnant Women Class class between post online and post offline. Discussion: Giving pregnant women classes before and after in the offline group has a good effect because there is an increase in the average knowledge of pregnant women. Conclusion: In providing health education both offline and online, there is no difference in the effectiveness of both the intervention group and the control group. Increasing mother's knowledge based on mother's understanding in receiving the information that has been given.